2020
DOI: 10.34172/aim.2020.114
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Clinical Symptoms, Laboratory Findings and Imaging of Pregnant Women Infected with COVID-19 in North of Iran

Abstract: Background: Due to the physiological changes in the body during pregnancy, the increased susceptibility to viral infections during this period and also the high prevalence of coronavirus disease 2019 (COVID-19) in the Guilan province, Iran, this study aimed to evaluate risk factors, clinical symptoms, laboratory findings and imaging of pregnant mothers with COVID-19. Methods: In this descriptive study, 70 pregnant women aged 17–41 years with COVID-19 who were hospitalized from early March to late April 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
3
1
7
Order By: Relevance
“…As complicações de parto mais prováveis de acontecer são: parto prematuro e parto cesariano de urgência 8,12,13,21,28,31,32 . Sendo este último o tipo de parto que mais está sendo feito durante a pandemia da COVID-19, tanto em sua forma leve como na moderada e na grave, apesar dos vaginais também ocorrerem 44 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As complicações de parto mais prováveis de acontecer são: parto prematuro e parto cesariano de urgência 8,12,13,21,28,31,32 . Sendo este último o tipo de parto que mais está sendo feito durante a pandemia da COVID-19, tanto em sua forma leve como na moderada e na grave, apesar dos vaginais também ocorrerem 44 .…”
Section: Discussionunclassified
“…Em gestantes, pneumonia por infecção advinda de qualquer etiologia tem significativa importância na morbidade e mortalidade, e é a infecção não obstétrica que mais comumente ocorre 7 . Devido às mudanças fisiológicas que ocorrem no organismo da mulher gestante, como enfraquecimento do sistema imunológico e alterações do trato respiratório, ela torna-se mais propícia a quadros de pneumonias mais severas 8 . O rebaixamento imunológico fisiológico se dá nos primeiros trimestres da gestação e é revertido no terceiro trimestre com ótima ativação e funcionalidade, esse evento ocorre com o objetivo de permitir o feto desenvolver-se 9,10 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…This is in accordance with other studies in the Middle East as well as in other worldwide countries such as the United States ( Hirshberg et al, 2020 ) and China ( Chen H et al, 2020 ). In Iranian pregnant women, the most common reported symptoms of COVID-19 were fever, cough, and dyspnea ( Kazemi Aski et al, 2020 , 2021 ; Motlagh et al, 2020 ; Pirjani et al, 2020 ; Sattari et al, 2020 ; Akbarian-Rad et al, 2021 ; Alipour et al, 2021 ; Samadi et al, 2021 ; Vaezi et al, 2021 ; Vizheh et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021b ). Lymphopenia and elevated C-reactive protein levels ( Pirjani et al, 2020 ; Akbarian-Rad et al, 2021 ; Vaezi et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a , b ), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020 ; Abedzadeh-Kalahroudi et al, 2021a ), were the most common laboratory findings observed.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…Lymphopenia and elevated C-reactive protein levels ( Pirjani et al, 2020 ; Akbarian-Rad et al, 2021 ; Vaezi et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a , b ), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020 ; Abedzadeh-Kalahroudi et al, 2021a ), were the most common laboratory findings observed. The SARS-CoV-2 infection in this population presented mainly as a mild-to-moderate disease ( Kazemi Aski et al, 2020 ; Vizheh et al, 2021 ). Samadi et al found that the presence of underlying medical conditions is significantly associated with disease severity of COVID-19.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%